Functional Neuroimaging: Single Photon Emission Computed Tomography (SPECT) In Neurological Disorders - Rahman, Aminur; Salam, Farhana; Begum , Rubina; Akhter, Afroza; Nabi, Shahryar; Rahman, Md Khalilur; Islam, Md Tariqul; Ali, Zahed; Saha, Uttam Kumar; Quraishi, Firoz Ahmed (Bangladesh Journal of Neuroscience, 2018)
A single photon emission computed tomography (SPECT) scan is a functional nuclear imaging technique performed to evaluate regional cerebral perfusion. Because cerebral blood flow is closely linked to neuronal activity, the activity distribution is presumed to reflect neuronal activity levels in several areas of the brain. Although structural magnetic resonance imaging (MRI) and computed tomography (CT) provide exquisite anatomical detail, SPECT provide complementary functional information. Frequently, brain pathology will manifest as functional changes before anatomical changes are detectable. SPECT has clinical value in the diagnosis, therapeutic management, and follow-up of patients. A general consideration of the clinical value of this technique is followed by relevant information on cerebral physiology and pathology for proper understanding of brain SPECT images. The diversity of central nervous system diseases and therefore the still incomplete knowledge of the mechanisms that underlie them have contributed to the success of brain perfusion SPECT as a research tool in neurosciences. Finally, stepby- step recommendations for interpreting and reporting brain perfusion SPECT images are provided to get the utmost clinical beneût from this technique. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 96-105